Determining fair remuneration based on human capital theory - Hynek, Olaf; Bik, Marcin (International Journal of Accounting and Economics Studies, 2020)
The text of Determining fair remuneration based on human capital theory contains useful informations about measurability human capital that can be used for personal use in any case of employment in any country. the text contains the essence of fair remuneration, the formulas needed to create it, and 2 examples of their application. Â